The Performance of Technology Industry Startup Employees In The Digital Era In Indonesia - Leonard, Bona Patrick; Aryana Satrya (Dinasti International Journal of Digital Business Management, 2023)
This study is aimed at testing the influence of motivation and organizational climate on employee performance through job satisfaction and employee attachment as mediating variables. This study uses a quantitative approach that highlights the relationship or influence between research variables and tests hypotheses, using primary data collected using the survey method through questionnaires with a liker scale of 1 to 5. The population in this study is Digital Startup Employees in Indonesia. The study sample numbered 265 people. Data analysis was carried out using descriptive statistical analysis and inferential statistical analysis (Structural Equation Modeling (SEM) using the Lisrel 8.80 program. The results showed that motivation, organizational climate, job satisfaction, and employee attachment had a positive and significant direct influence on job satisfaction; Motivation and organizational climate have a significant positive influence on job satisfaction and employee engagement. Job satisfaction and employee engagement as mediating variables increase the relationship between motivation and organizational climate to employee performance.